2007
DOI: 10.2166/wh.2007.034
|View full text |Cite
|
Sign up to set email alerts
|

Cost and financial sustainability of a household-based water treatment and storage intervention in Zambia

Abstract: Providing safe water to .1 billion people in need is a major challenge. To address this need, the Safe Water System (SWS) -household water treatment with dilute bleach, safe water storage, and behavior change -has been implemented in .20 countries. To assess the potential sustainability of the SWS, we analyzed costs in Zambia of "Clorin" brand product sold in bottles sufficient for a month of water treatment at a price of $0.09. We analyzed production, marketing, distribution, and overhead costs of Clorin befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Evaluations of other HWTS strategies in programmatic settings have also reported low levels of adoption [30],[40],[41], while research-driven studies have found higher levels of reported use [42]. Further research is needed to better understand how to achieve consistent and sustained adoption of these interventions on a programmatic basis and over the long term.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluations of other HWTS strategies in programmatic settings have also reported low levels of adoption [30],[40],[41], while research-driven studies have found higher levels of reported use [42]. Further research is needed to better understand how to achieve consistent and sustained adoption of these interventions on a programmatic basis and over the long term.…”
Section: Discussionmentioning
confidence: 99%
“…There exist several reviews and studies of the costs of health intervention programmes which address the prevention of climate-related diarrhea and cholera [20,21,22,23,24]. These studies present measures to reduce vulnerability to current events.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Although tens of millions of people rely on improved community water supplies, water supply authorities may not deliver microbiologically qualified water, so water needs to be treated at the household level. 17,18 In low-income countries, numerous household water treatments (HWT) have been confirmed to significantly improve drinking water quality in field trials. 19 It was reported that there was more than 25% reduction in diarrheal disease among children <2 years of age using flocculent disinfectant compared to untreated water handling methods.…”
Section: Introductionmentioning
confidence: 99%